2021
DOI: 10.1186/s40463-020-00487-6
|View full text |Cite
|
Sign up to set email alerts
|

Noise in Otolaryngology – Head and Neck Surgery operating rooms: A systematic review

Abstract: Objective Noise in operating rooms (OR) can have negative effects on both patients and surgical care workers. Noise can also impact surgical performance, team communication, and patient outcomes. Such implications of noise have been studied in orthopedics, neurosurgery, and urology. High noise levels have also been demonstrated in Otolaryngology-Head and Neck Surgery (OHNS) procedures. Despite this, no previous study has amalgamated the data on noise across all OHNS ORs to determine how much no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This level was deemed to be in excess of safety thresholds. 11 Moreover, in a study examining noise levels in total knee and hip arthroplasty, the peak noise level during surgery measured more than 140 dB. Although noise exposure throughout these surgeries remained within occupational standards, the mean percentage of allowed daily noise reached 40% in the surgeons performing these cases.…”
Section: Discussionmentioning
confidence: 99%
“…This level was deemed to be in excess of safety thresholds. 11 Moreover, in a study examining noise levels in total knee and hip arthroplasty, the peak noise level during surgery measured more than 140 dB. Although noise exposure throughout these surgeries remained within occupational standards, the mean percentage of allowed daily noise reached 40% in the surgeons performing these cases.…”
Section: Discussionmentioning
confidence: 99%
“…a systematic review on eNt surgery reported that occupational exposure to noise can reach unsafe levels. 25 limit of acceptable exposure in the 2005 Hse regulations. 8 chen et al 4 reviewed the levels of noise in different surgical specialities, including orthopaedics, in 18 operating theatres for the Usa National institute for Occupational safety and Health.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of noise exposure during otolaryngology and head and neck surgery showed that the maximum noise level was 95.5 dB, and the average noise level was 70.1 dB 19 . The average noise level of abdominal surgery also exceeded the recommended maximum noise level of 55 dB 14 .…”
Section: Discussionmentioning
confidence: 99%